Analisis Hukum Judi Online dalam Perspektif Maqāṣid Al-Syarī‘ah - Laili, Adinda Nuril; Azzahra, Fadhilatun Ni'mah; Alfina, Ishmah Tahta (Sharia Journal and Education Center Publishing, 2026)
This article aims to discuss the law of online gambling from the perspective of maqashid shari'ah. The research of this article uses a qualitative approach with the type of library research. The data collection techniques used are documentation, data analysis techniques used in content analysis, induction, and deduction. Online gambling is any form of betting game that uses money or valuable assets, done online through a website or internet application. This activity involves speculating on uncertain outcomes such as slots, casinos, or sports betting and is illegal under the ITE Law in Indonesia. Online gambling in Indonesia poses a variety of complex social and economic problems. Online gambling not only impacts individual financial losses, but also triggers moral breakdown, family dysfunction, and increased crime. Maqashid shari'ah here aims to protect the basic interests of human beings including religion, soul, intellect, property, and descendants. This is to ensure that what they do does not contradict the principles of Islam. Online gambling is very detrimental to everyone because it has a great impact on all aspects protected in the maqashid shari'ah. Some ways to overcome online gambling so that it is not too rampant are the implementation of tighter laws, education for everyone about the dangers of online gambling, and more tightening the use of citizens in accessing online gambling applications.